Vibrational spectroscopy studies of formalin-fixed cervix tissues - Krishna, C. M.; Sockalingum, G. D.; Vadhiraja, B. M.; Maheedhar, K.; Rao, A. C. K.; Rao, L.; Venteo, L.; Pluot, M.; Fernandes, D. J.; Vidyasagar, M. S.; Kartha, V. B.; Manfait, M. (Biopolymers, 2007)
Optical histopathology is fast emerging as a potential tool in cancer diagnosis. Fresh tissues in saline are ideal samples for optical histopathology. However, evaluation of suitability of ex vivo handled tissues is necessitated because of severe constraints in sample procurement, handling, and other associated problems with fresh tissues. Among these methods, formalin‐fixed samples are shown to be suitable for optical histopathology. However, it is necessary to further evaluate this method from the point of view discriminating tissues with minute biochemical variations. A pilot Raman and Fourier transform infrared (FTIR) microspectroscopic studies of formalin‐fixed tissues normal, malignant, and after‐2‐fractions of radiotherapy from the same malignant cervix subjects were carried out, with an aim to explore the feasibility of discriminating these tissues, especially the tissues after‐2‐fractions of radiotherapy from other two groups. Raman and FTIR spectra exhibit large differences for normal and malignant tissues and subtle differences are seen between malignant and after‐2‐fractions of radiotherapy tissues. Spectral data were analyzed by principal component analysis (PCA) and it provided good discrimination of normal and malignant tissues. PCA of data of three tissues, normal, malignant, and 2‐fractions after radiotherapy, gave two clusters corresponding to normal and malignant + after‐2‐fractions of radiotherapy tissues. A second step of PCA was required to achieve discrimination between malignant and after‐2‐fractions of radiotherapy tissues. Hence, this study not only further supports the use of formalin‐fixed tissues in optical histopathology, especially from Raman spectroscopy point of view, it also indicates feasibility of discriminating tissues with minute biochemical differences such as malignant and after‐2‐fractions of radiotherapy. © 2006 Wiley Periodicals, Inc. Biopolymers 85: 214–221, 2007. This article was originally published online as an accepted preprint. The “Published Online” date corresponds to the preprint version. You can request a copy of the preprint by emailing the Biopolymers editorial office at biopolymers@wiley.com